A6_5 Apparent Magnitudes of "Jupitershine" - Chowdhury, Mohammad Nahid; Watters, Daniel; Mucesh, Sunil; Nutting, Darren (Physics Special Topics, 2016)
We use solar irradiance and solid angle to estimate the planetshine apparent magnitudes of the Galilean moons. We estimate these to be -4.79 for Io, -2.54 for Europa, -1.17 for Ganymede and 2.38 for Callisto.